Pola Interaksi Guru dan Siswa Tunanetra - Widyastuti, Rany (Universitas Islam Raden Intan Lampung, INDONESIA, 2016)
This study aims to describe the pattern of interaction between teachers and students and between students with other students on learning VII grade SMPLB A Bina Insani Bandar Lampung. This research is a qualitative research. The subject of this research is one teacher and all students of class VII SMPLB A Bina Insani Bandar Lampung, amounting to 5 people where 1 student is light blind (low vision) and 4 students total blind. The technique of validity of data used is by triangulation time, that is by seeing the data of an interaction between a teacher with the student and between student on two observations done on a different day. The results of this study indicate that the pattern of interaction of teachers and students with visual impairment in learning VII grade SMPLB A Bina Insani Bandar Lampung is a two-way interaction but without the interaction between students with one student, either in the category of information (BIn) (UIn), as well as delay information (TIn).